THE INFLUENCE OF RISK MANAGEMENT, HR QUALITY AND WORKLOAD ON THE ABILITY TO DETECT FRAUD IN LOCAL GOVERNMENT INSPECTORATES IN NORTH SUMATRA - Annisa Ramadhani; Erlina; Azizul Kholis (CV. Radja Publika, 2023)
This study intends to test and analyze whether the variables of Implementation of Risk Management, Quality of Human Resources, and Workload affect the Auditor's Ability to Detect Fraud either partially or simultaneously. The population of this study are internal auditors in provinces, districts and cities in North Sumatra. The method used is a survey method by distributing questionnaires using the Google form and is a causality study. Respondents amounted to 184 Auditor Functional Officers who worked at the North Sumatra Regional Government Inspectorate. Determination of the sample using a simple random technique. The research design built is multiple linear regression analysis. The data collected by the researchers was processed using the PLS and SPSS applications. The results of the study show that the implementation of risk management variables, The quality of human resources and workload have an effect on the auditor's ability to detect fraud, both partially and simultaneously, have a simultaneous effect on the ability to detect fraud. Partially, the implementation of risk management and quality of human resources has a unidirectional (positive) relationship and has a significant effect on the auditor's ability to detect fraud, while workload has a negative and insignificant relationship.